Real and invented islands in the 20th century Ukrainian literature as the elements of existential imagery - Naumenko, Nataliia (My University, 2022)
This article examines the development of mythical chronotopical image of an island in the works dated by the first third of the 20th century, which was a period of not only great historical collisions of both natural and anthropogenous origin, but also experiencing their consequences. Based on George Hegel’s hypothesis ‘history will teach us nothing,’ we find it relevant to turn back to belle-lettres works that can impact the contemporary’s consciousness maybe stronger than historical writings. The image of the island is taken as a conceit to outgo far beyond pure geographical terminology and therefore embody an array of archetypal notions, including loneliness, dreams and mystery, separate being, and precisely outlined space. The result of this research is the establishment of the new connotations of the motif of ‘an island’ as the concentration of archetypal binary oppositions reality / illusion, quietness / anxiety, idyllic existence / survival, comedy / tragedy, internal / external in poetic and prosaic works of the noticed period.
Keywords: кафедра іноземних мов професійного спрямування; острів; хронотоп; міф; українська література ХХ століття; дійсність; ілюзія; образ; island; chronotopos; myth; the 20th century Ukrainian literature; reality; illusion; image